Clinical Profile of Patients with Anemia in a Tertiary Care Hospital - Aryal, Deepak; Ghimire, Mahesh Raj; Pandey, Sundar; Paudel, Deepak; Gaire, Ashmita (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Anemia is a common health problem with nonspeciﬁc symptoms often overlooked leading to adverse health outcomes. This study aims to assess the clinical proﬁle, types, and etiologies of anemia. MATERIAL AND METHODS In this hospital based cross-sectional study, patients with anemia were enrolled through convenience sampling. Relevant history, physical examination, and investigations were performed. Statistical package for social sciences software version 20 was used to enter and analyze the data. Categorical variables were expressed as frequencies and percentages. Continuous variables were expressed as median (range). The associations were analyzed by using Fisher's exact test or Chi-square test, as appropriate. RESULTS Out of 193 patients, 151 (78.2%) were females. The median age was 49 years (range 18-87 years). Most frequent symptoms were easy fatiguability (76.2%), breathlessness on exertion (30.1%), and light headedness (21.8%). Most frequent signs were pallor (75.6%), tachycardia (23.8%), glossitis (16.1%), and nail changes (15.5%). Majority (79.3%) had moderate and 17.1% had severe anemia. Iron deﬁciency (59.1%) and anemia of inﬂammation (28%) were common etiologies. Iron deﬁciency anemia was most commonly due to nutritional deﬁciency. Age was signiﬁcantly associated with the type and etiology of anemia. CONCLUSION Moderate anemia was the most common presentation. Easy fatiguability, breathlessness on exertion, and light headedness were most common symptoms, while pallor, tachycardia, glossitis, and nail changes were the most common signs. Iron deﬁciency anemia and anemia of inﬂammation were most common etiologies. Iron deﬁciency anemia was more common in younger patients, while anemia of inﬂammation was more common in older patients.